Litter and root traits control soil microbial composition and enzyme activities in 28 common subtropical tree species. (17th October 2022) - Wan, Xiaohua; Yu, Zaipeng; Wang, Mengjuan; Zhang, Yu; Huang, Zhiqun
Abstract: Plant trait‐based approaches are frequently used to explore the linkages between above‐ground plant communities and below‐ground ecosystem functions. However, the role of plant leaf litter and living root traits in driving soil microbial biomass, community composition and enzyme activities has rarely been explored. Here, we measured the soil microbial biomass, community composition and enzyme activities related to carbon (C), nitrogen (N) and phosphorus (P) acquisition under 3‐year‐old monocultures of 28 common subtropical tree species in China. We found that plant leaf litter and absorptive root traits, including leaf litter C content, litter water holding capacity and root N content, were the three best predictors for soil microbial biomass and enzyme activities. In particular, resource‐exploitative tree species with higher root N contents were associated with microbial communities with lower fungi to bacteria ratios and lower C‐ and P‐acquisition enzyme activities. Tree species with higher leaf litter water holding capacity were associated with microbial resource acquisition strategies for C and P acquisition. Synthesis : Our findings highlighted that plant leaf litter and root traits are important for mechanistically understanding the ecological linkage between the plant community and ecosystem functions. Abstract : Our findings highlighted that plant leaf litter and root traits are important for mechanistically understanding the ecological linkage between the plant community and ecosystem functions. Abstract : 树种与土壤微生物群落之间的相互作用是维持生态系统多种功能的关键。以往关于植物群落与地下生态系统过程的关系研究大多利用叶片功能性状来解释，但是在森林生态系统里面，很多学者发现叶片功能特征与土壤微生物群落组成之间的联系较弱。由于根系和凋落物直接与土壤微生物接触，因此研究根系和凋落物特征如何驱动微生物组成与功能变化对于理解树种与生态系统功能之间的生态联系具有重要的意义。2019年3月我们在中国的南亚热带地区建立了一个树种多样性与生态系统功能野外实验，选择其中的28个树种纯林，我们测定了15个植物功能性状:叶片碳、叶片氮、比叶面积、叶干物质含量、凋落叶碳、凋落叶氮、凋落叶木质素、纤维素、浓缩单宁含量、凋落叶pH值，凋落叶最大持水率、细根碳、细根氮、细根直径和比根长。采用磷脂脂肪酸方法测定土壤微生物生物量和群落组成，同时分析与碳、氮、磷降解有关的5种酶活性。研究结果发现，凋落叶碳含量、最大持水率和根系氮含量是解释土壤微生物群落组成和酶活性变化的重要因子。土壤总的微生物生物量随着凋落叶碳含量、最大持水率的增加而增加；资源开发型树种根系氮含量较高，其微生物群落具有较低的真细菌比和较低的氮、磷降解酶活性；凋落叶持水能力高的树种，其土壤微生物碳、磷降解酶活性较高。我们的研究揭示了根系和凋落物功能特性对于理解植物群落与地下微生物群落组成和功能的生态联系具有重要意义。这一发现对于改进植物群落变化的生态系统功能预测至关重要。